Binding of cryptococcal polysaccharide to Cryptococcus neoformans. - Kozel, T R (1984)
Radioiodinated cryptococcal polysaccharide was used to study binding of the soluble polysaccharide to encapsulated and non-encapsulated cryptoccoci. Binding of polysaccharide to non-encapsulated cryptococci occurred rapidly over a 30-min period and was largely complete after 2 h. Bound, labeled polysaccharide was slowly eluted from Cryptococcus neoformans after the addition of unlabeled polysaccharide, indicating reversibility of binding. Non-encapsulated cryptococci bound polysaccharide in two ways. Specific binding to the yeast was saturable by ca. 82 ng of polysaccharide per 10(6) yeast cells. Nonspecific binding also occurred which was not saturable under the conditions used in our experiments. Phagocytosis of the non-encapsulated yeast strain was inhibited when the specific binding was ca. 50% saturated. Binding of polysaccharide to an encapsulated strain showed nonspecific, nonsaturable binding, but little specific binding occurred. Presumably the specific binding sites were saturated in the encapsulated strain. Polysaccharides obtained from a hypocapsular mutant (A61) and a normally encapsulated strain competed effectively with labeled serotype D polysaccharide for binding sites on non-encapsulated cryptococci and had identical phagocytosis-inhibiting properties. Similarly, polysaccharides from all four cryptococcal serotypes competed effectively with labeled serotype D polysaccharide for binding sites on the non-encapsulated strain, and all four polysaccharides inhibited phagocytosis of non-encapsulated Cryptococcus neoformans. Unmodified, de-O-acetylated, carboxyl-reduced, periodate-oxidized and reduced (polyalcohol), and Smith-degraded polysaccharides competed with labeled polysaccharide for binding sites on the cell. The unmodified, de-O-acetylated and carboxyl-reduced polysaccharides inhibited phagocytosis of non-encapsulated cells, but the polyalcohol and Smith product were unable to inhibit phagocytosis.